Relation Between Mechanical Properties and 3D Printer Configurations Parameters Using PLA at Open-Source Prusa I3 - Sierra, Jorge; Sanin Villa, Daniel; Montoya Velasquez, Andres; Villaneda, Walter (International Journal of Integrated Engineering, 2020)
This paper presents an experimental study on specimens made with the additive manufacturing (AM) Fused Deposition Material (FDM) technique with PLA material. Several configurations of geometry and printing temperature were made in order to evaluate these parameters over a tensile test. The geometry of the specimen was fabricated according to the ASTM D638 and the curvature of fillet radius were varied (76-std, 144, 244mm and straight) to obtain optimal fillet radius for tensile test. The nozzle temperature was varied (200, 210, 220 and 230Â°C) to show its influence on PLA stress-strain behavior. Results have shown that the fillet radius of the specimen and the printer parameters affect material quantity deposited during 3D printing process, leaving to progressive damage areas. Better performance was obtained at 210 Â°C printing temperature with a fillet radius of 144 mm. A modification geometry specimen were proposed in order to change the increase Z nozzle level point that generates a stress concentrator at the specimen avoiding failure zone at calibrating length of the specimen.